Analisis Hukum Waris Islam terhadap Pasal 177 KHI dan SEMA No. 2 Tahun 1994 tentang Besar Bagian Waris Ayah - Refsi Inggranawat; Shindu Irwansyah (UPT Publikasi Ilmiah Unisba, 2021)
Abstract. Q.S. An-Nisa: 11, 12, and 176 are the basis of inheritance law. Q.S.An-Nisa: 11 describes the inheritance of parents when the testator does not leave the child, the mother gets 1/3 part, while the rest of the father. However, KHI brings up 1/3 part for the father when the heir does not leave the child. Against this decree, SEMA was born No. 2 of 1994 as an explanation of the meaning of article 177 KHI so that the sound of article 177 changes to: